UNCCD COP 16: Global actions for sustainable rangelands and pastoralism to achieve Land Degradation Neutrality - Louhaichi, Mounir (2025)
The presentation by Mounir Louhaichi, on behalf of the IYRP Rangelands & Land Degradation Neutrality Working Group, was delivered during the Road to the International Year of Rangelands and Pastoralists (IYRP) 2026 session at COP 16 in KSA. It outlined critical recommendations for enhancing rangeland management and promoting pastoralism within the framework of Land Degradation Neutrality (LDN). The presentation emphasized the urgent need to halt the indiscriminate conversion of rangelands, recognized pastoral mobility as essential for ecosystem health, and advocated for the implementation of innovative economic policies that benefit both rangelands and pastoralists. Additionally, it called for integrated land-use approaches, stronger governance, and increased funding for rangeland projects. The presentation also urged for the inclusion of rangeland restoration in global LDN targets and the establishment of participatory knowledge-sharing practices.